Automated segmentation of Acute Lymphocytic Leukemia (ALL) subtypes by the combination of color space conversion and K-means cluster - Hersh Muhsin Osman; Sardar Pirkhider Yaba (Zanco Journal of Pure and Applied Sciences, 2022)
Leukemia is blood cancer, and it is one of the most common and deadly causes of death in the world. Morphologically, Leukemia cells are classified into three types of L1, L2, and L3 by the French‑American‑British (FAB) classification. A new method of automatically segmenting blast cells from microscopic blood smear images proposed in this research. This study proposes significant pre-processing to obtain high segmentation performance and presents a new combination of image processing approaches. specially, the five color spaces selected with K-means cluster to segment subtypes of Acute Lymphocytic Leukemia. The majority of the components of the performance color space were chosen based on their similarity with ground truth image through using five evaluation parameters. The proposed codes for Acute Lymphocytic Leukemia subtype accurate segmentation applied on local and public datasets (427 images). The best color space type was YIQ which had 87% performance for the public dataset with segmentation evaluation 96.24% for dice parameter References AL-JABORIY, S. S., SJARIF, N. N. A., CHUPRAT, S. & ABDUALLAH, W. M. 2019. Acute lymphoblastic leukemia segmentation using local pixel information. Pattern Recognition Letters, 125, 85-90. AL HAMAD, H. A. Use an efficient neural network to improve the Arabic handwriting recognition. 2013 IEEE International Conference on Signal and Image Processing Applications, 2013. IEEE, 269-274. AMIN, M. M., KERMANI, S., TALEBI, A. & OGHLI, M. G. 2015. Recognition of acute lymphoblastic leukemia cells in microscopic images using k-means clustering and support vector machine classifier. Journal of medical signals and sensors, 5, 49. ASHOUR, A. S., WAHBA, M. A. & GHANNAM, R. 2021. A Cascaded Classification-Segmentation Reversible System for Computer-aided Detection and Cells Counting in Microscopic Peripheral Blood Smear Basophils and Eosinophils Images. IEEE Access. ASLAN, M. S., MOSTAFA, E., ABDELMUNIM, H., SHALABY, A., FARAG, A. A. & ARNOLD, B. A novel probabilistic simultaneous segmentation and registration using level set. 2011 18th IEEE International Conference on Image Processing, 2011. IEEE, 2161-2164. BHIMANI, J., LEESER, M. & MI, N. Accelerating K-Means clustering with parallel implementations and GPU computing. 2015 IEEE High Performance Extreme Computing Conference (HPEC), 2015. IEEE, 1-6. GHANE, N., VARD, A., TALEBI, A. & NEMATOLLAHY, P. 2017. Segmentation of white blood cells from microscopic images using a novel combination of K-means clustering and modified watershed algorithm. Journal of medical signals and sensors, 7, 92. HEGDE, R. B., PRASAD, K., HEBBAR, H. & SINGH, B. M. K. 2019. Image processing approach for detection of leukocytes in peripheral blood smears. Journal of medical systems, 43, 1-11. KADRY, S., RAJINIKANTH, V., TANIAR, D., DAMAŠEVIČIUS, R. & VALENCIA, X. P. B. 2021. Automated segmentation of leukocyte from hematological images—a study using various CNN schemes. The Journal of Supercomputing, 1-21. KARWAN, M., ABDULLAH, O., AMIN, A., HASAN, B., MOHAMED, Z., SULAIMAN, L., SHEKHA, M., NAJMULDEEN, H., BARZINGI, B. & SALIH, A. 2021. Cancer Statistics in Kurdistan Region of Iraq: A Tale of Two Cities. LABATI, R. D., PIURI, V. & SCOTTI, F. 2011. The Acute Lymphoblastic Leukemia Image Database for Image Processing. Universita Degli Studi Di Milano, 10. MILLER, D. R., LEIKIN, S., ALBO, V., SATHER, H. & HAMMOND, D. 1981. Prognostic importance of morphology (FAB classification) in childhood acute lymphoblastic leukaemia (ALL). British Journal of Haematology, 48, 199-206. PHILIP, A. T., SHIFAANA, S., SUNNY, S. & MANIMEGALAI, P. Detection of Acute Lymphoblastic Leukemia in Microscopic images using Image Processing Techniques. Journal of Physics: Conference Series, 2021. IOP Publishing, 012022. PRABHA, D. S. & KUMAR, J. S. 2016. Performance evaluation of image segmentation using objective methods. Indian J. Sci. Technol, 9, 1-8. SARRAFZADEH, O., DEHNAVI, A. M., RABBANI, H. & TALEBI, A. A simple and accurate method for white blood cells segmentation using K-means algorithm. 2015 IEEE Workshop on Signal Processing Systems (SiPS), 2015. IEEE, 1-6. SHAFIQUE, S. & TEHSIN, S. 2018. Acute lymphoblastic leukemia detection and classification of its subtypes using pretrained deep convolutional neural networks. Technology in cancer research & treatment, 17, 1533033818802789. SIEGEL, R. L., MILLER, K. D., GODING SAUER, A., FEDEWA, S. A., BUTTERLY, L. F., ANDERSON, J. C., CERCEK, A., SMITH, R. A. & JEMAL, A. 2020. Colorectal cancer statistics, 2020. CA: a cancer journal for clinicians, 70, 145-164. TAVAKOLI, E., GHAFFARI, A., KOUZEHKANAN, Z. M. & HOSSEINI, R. 2021. New Segmentation and Feature Extraction Algorithm for Classification of White Blood Cells in Peripheral Smear Images. bioRxiv. TSAI, C.-M. & LEE, H.-J. 2002. Binarization of color document images via luminance and saturation color features. IEEE Transactions on Image Processing, 11, 434-451. ZOU, K. H., WARFIELD, S. K., BHARATHA, A., TEMPANY, C. M., KAUS, M. R., HAKER, S. J., WELLS III, W. M., JOLESZ, F. A. & KIKINIS, R. 2004. Statistical validation of image segmentation quality based on a spatial overlap index1: scientific reports. Academic radiology, 11, 178-189.